Comparison of attribute selection methods for web texts categorization - Saian, Rizauddin; Ku-Mahamud, Ku Ruhana (2010)
This paper presents a study on the performance of attribute selection methods to be used with Ant-Miner algorithm for web text categorization.The new generated data set by each attribute selection method was classified with Ant-Miner to see the performance in terms of predictive accuracy and the number of rules generated.The results of classification were also compared to C4.5 algorithm.